Curvature detection with an optoelectronic measurement system using a self-made calibration profile - Thorwartl, C.; Stöggl, T.; Teufl, W.; Holzer, H.; Kröll, J. (Sensors, 2022)
So far, no studies of material deformations (e.g., bending of sports equipment) have been performed to measure the curvature (w?) using an optoelectronic measurement system OMS. To test the accuracy of the w measurement with an OMS (Qualisys), a calibration profile which allowed to: (i) differentiates between three w (0.13 m-1, 0.2 m-1, and 0.4 m-1) and (ii) to explore the influence of the chosen infrared marker distances (50 mm, 110 mm, and 170 mm) was used. The profile was moved three-dimensional at three different mean velocities (vzero = 0 ms-1, vslow = 0.2 ms-1, vfast = 0.4 ms-1) by an industrial robot. For the accuracy assessment, the average difference between the known w of the calibration profile and the detected w from the OMS system, the associated standard deviation (SD) and the measuring point with the largest difference compared to the defined w (=maximum error) were calculated. It was demonstrated that no valid w can be measured at marker distances of 50 mm and only to a limited extent at 110 mm. For the 170 mm marker distance, the average difference (±SD) between defined and detected w was less than 1.1 ± 0.1 mm-1 in the static and not greater than -3.8 ± 13.1 mm-1 in the dynamic situations. The maximum error in the static situation was small (4.0 mm-1), while in the dynamic situations there were single interfering peaks causing the maximum error to be larger (-30.2 mm-1 at a known w of 0.4 m-1). However, the Qualisys system measures sufficiently accurately to detect curvatures up to 0.13 m-1 at a marker distance of 170 mm, but signal fluctuations due to marker overlapping can occur depending on the direction of movement of the robot arm, which have to be taken into account.